2019
DOI: 10.1002/cpe.5455
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of a physical activity energy expenditure with a patch‐type sensor module using artificial neural network

Abstract: Chronic diseases such as coronary artery diseases and diabetes are caused by lack of physical activities and are leading causes of high death and morbidity rates. In particular, the imbalance of consumption energy and intake energy has increased adult diseases such as obesity with high mortality. Until recently, direct calorimetry by production calorie and indirect calorimetry by energy expenditure have been regarded as the best methods for estimating physical activity and energy expenditure. These calorimetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Details on the use of AI for the self-regulation of weight lossrelated behaviours are shown in Table 2. Of the studies on enhancing self-monitoring, twenty-nine (43•9 %) were on eating behaviours (58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76) , seven (10•6 %) were on energy intake (34,(77)(78)(79)(80)(81)(82) , thirty-three (50 %) were on physical activity (26,(51)(52)(53)(54)(55)60,74, and nine (13•6 %) were on energy expenditure (83,85,92,(94)(95)(96)(97)100,101) . Of the studies on optimising goal setting, five were on optimising eating behaviour goals (e.g., eating at a certain time of the day and energy intake) (48,49,53) and six were on optimising physical activity...…”
Section: Self-regulation Of Weight Loss-related Behavioursmentioning
confidence: 99%
See 3 more Smart Citations
“…Details on the use of AI for the self-regulation of weight lossrelated behaviours are shown in Table 2. Of the studies on enhancing self-monitoring, twenty-nine (43•9 %) were on eating behaviours (58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76) , seven (10•6 %) were on energy intake (34,(77)(78)(79)(80)(81)(82) , thirty-three (50 %) were on physical activity (26,(51)(52)(53)(54)(55)60,74, and nine (13•6 %) were on energy expenditure (83,85,92,(94)(95)(96)(97)100,101) . Of the studies on optimising goal setting, five were on optimising eating behaviour goals (e.g., eating at a certain time of the day and energy intake) (48,49,53) and six were on optimising physical activity...…”
Section: Self-regulation Of Weight Loss-related Behavioursmentioning
confidence: 99%
“…The studies reported recognition accuracies ranging from 69•2 to 99•1 %. Machine recognition techniques used in the included studies were gesture (n 32) (51,56,58,(60)(61)(62)64,65,70,74,81,(83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(95)(96)(97)(98)(99)(100)(101)(102)(103)(104) , image (n 14) (34,63,(66)(67)(68)74,76,(78)(79)(80)88,93,94,101) , sound (n 7) (57)(58)(59)69,(71)(72)…”
Section: Machine Perception: Self-monitoringmentioning
confidence: 99%
See 2 more Smart Citations
“…In Estimation of a physical activity energy expenditure with a patch‐type sensor module using artificial neural network by Kang et al, 11 it proposed the most accurate method using a wireless patch‐type sensor to predict the energy expenditure of physical activities. Through the optimization of the prediction of energy expenditure of physical activities using the neural network algorithm, it achieved RMSE of 0.1893, R2 of 0.91 for the energy expenditures of aerobic and anaerobic exercises.…”
Section: Introductionmentioning
confidence: 99%